Scientific Elites Influence on Political Process in Russia (First Results of Empirical Research) - Lyakhovenko, Oleg (Visnyk of V. N. Karazin Kharkiv National University. Series Sociological studies of contemporary society: methodology, theory, methods, 2019)
The issue of the role and participation of the scientific elite in the political process in Russia is at the junction of practical analysis of the postulates of theories of "postindustrial society" and "knowledge society", from one side, and theoretical and conceptual generalization of established social and political practices of decision making – from the other one. Participation in decision-making practice has very specific features: to a large degree it has not reached the level of formal institutionalization, the ability of scientific elite to influence the strategic decisionmaking process; also its recruitment to the political class is limited. At the same time, the influence of the scientific elite can be described as significant at the stage of implementation of elaborated solutions and also during analytical maintenance of current operational activity of public authorities.